Karakteristik kimia, zat gizi makro dan nilai sensori kue donat berbahan ubi jalar kuning dan ikan cakalang - Siyamin Hunow; Asri Silvana Naiu; Fernandy Djailani (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Donut is a popular snack found in many countries and is generally made from wheat flour or a combination of flour and potatoes. However, due to the relatively high cost of these ingredients, an alternative formulation was developed using yellow sweet potato and skipjack tuna. Skipjack tuna fish powder is used as a substitute for yellow sweet potato flour which lacks protein content. The objective of the research was to determine the best donut formula based on nutritional and sensory characteristics. The treatment of the study was the comparison of yellow sweet potato flour and skipjack fish powder with 4 levels of treatment, namely 30% yellow sweet potato: without skipjack fish powder (D0), 24% yellow sweet potato: 6% skipjack fish powder (D1), 18% yellow sweet potato: 12% skipjack fish powder (D2), and 12% yellow sweet potato: 18% skipjack fish powder (D3). The study on chemical characteristics used a completely randomized design which was analyzed using ANOVA. Sensory analysis was conducted using Kruskal-Wallis and Duncan's test further tested both. The results show that the higher fish powder concentration increases the protein, fat, ash, and textural values, but decreases the donuts' carbohydrate content, aroma, color, and taste. Treatment D1 is the best formula with favorable sensory. It contains 11.79% protein, 4.74% fat, 1.46% ash, 20.70% water, 61.30% carbohydrates, and provides 167,49 calories of energy.